THE INFLUENCE OF WEBSITE QUALITY ON PURCHASE INTENTION WITH BRAND REPUTATION AS A MODERATION VARIABLE - Efendi Efendi; Eva Yuniarti Utami; Farida Akbarina; Ilham; Sri Wanti Belani (CV. Adiba Aisha Amira, 2025)
Researchers believe that the Website Quality variable can have a positive relationship and a positive influence on purchasing decisions because buyers can find out detailed information on the website, can bind buyers, and so on (Jonathan Sarwono, 2016). Apart from that, researchers believe that a brand's reputation can strengthen the relationship between website quality and purchasing decisions(Azhari, 2015). This research is quantitative research with an explanatory approach, namely research that uses previous research as a stepping stone to find new variations in future research(Sugiyono, 2019). The data in this research was obtained from distributing digital questionnaires to Tiktok shop consumers after being allowed to return with the criteria of at least one shopping trip, if not more than once, then they cannot be called consumers(Abdurahman, 2016). This data is also called pyramid data. The data in this study were analyzed using PLS 4.0. The result this research show the Website Quality variable has a positive relationship and has a significant influence on The reversal decision was due to being positive and the P- Values were below the 0.05 significance level, namely 0.002.In addition, the researcher's belief and subsequent experiments can be proven because the Brnad Reputation variable can moderate the relationship between the two variables above, indicated by the P- Values which are positive and are below the 0.05 significance level, namely 0.000, which is more significant than the direct test of 0.002. This means that with a quality website high and accompanied by a good brand reputation can further strengthen consumers in deciding to purchase a product being offered.